2019
DOI: 10.5603/gp.2019.0032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the treg cell population in the peripheral blood of ovarian cancer patients in relation to the long-term outcomes

Abstract: Objectives: There is growing evidence that Treg cell infiltration into the cancer nest is associated with poor prognosis. However, the Treg cell population in the peripheral blood may change when a different type of anticancer therapy is applied. Since Treg cells may support tumor growth by enhancing the suppressive profile of the cancer microenvironment, the assessment of Treg cells can bring to light important information regarding prognosis. Thus we decided to analyze the Treg cell population in the periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…VEGF-induced MDSCs inhibit the activity of CD8 + T cells in ovarian cancer, weakening the host's antitumor immune response and leading to a poor prognosis (54). A study showed that a higher count of Treg cells could be detected in the peripheral blood of patients with ovarian cancer and thus is associated with poor prognosis (55).…”
Section: Cell Signaling and Exosome-mediated Tumor Immune Microenviromentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF-induced MDSCs inhibit the activity of CD8 + T cells in ovarian cancer, weakening the host's antitumor immune response and leading to a poor prognosis (54). A study showed that a higher count of Treg cells could be detected in the peripheral blood of patients with ovarian cancer and thus is associated with poor prognosis (55).…”
Section: Cell Signaling and Exosome-mediated Tumor Immune Microenviromentioning
confidence: 99%
“…Tregs negatively regulate the antitumor response in both a direct and indirect manner while also playing a key role in immune escape (162). The increase of Tregs in the tumor microenvironment of patients is related to poor prognosis and shortened overall survival (OS) time (55). Treg-derived exosomes can exert immunosuppressive effects by expressing CD73 and inhibiting the proliferation of CD4 + T cells (107).…”
Section: Immunosuppressive Effector Cellsmentioning
confidence: 99%
“…Liu et al suggested that higher percent of circulating CD4+CD25+CD127 T cells can predict OS and chemotherapeutic response in patients with unresectable pancreatic cancer [27]. Dutsch-Wicherek et al also found that patients with serous adenocarcinomas had significantly CD25+ lymphocytes T levels compared to those patients with non-serous types [26]. There analyses identified CD25 may be attributable to the plasticity of T cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis indicated that CD25 overexpression is an indicator of poor prognosis for patients with AML. Where the majority of research had focused on hematological malignancies [ 25 ], there have been studies paying attention to the prognostic value of CD25 in solid tumors [ 26 – 28 ]. Liu et al suggested that higher percent of circulating CD4+CD25+CD127 T cells can predict OS and chemotherapeutic response in patients with unresectable pancreatic cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Zombie red Fixable Viability Kit BioLegend was used to exclude dead cells, according to the manufacturer s protocol. Following the staining of surface antigens, intracellular Foxp3 staining was performed using a Transcription Factor Buffer set BD Biosciences 13 . For intracellular IL-10 staining, a single cell suspension was incubated with LPS 10 µg/ml , PMA 50 ng/ml , ionomycin 500 ng/ml , and Brefeldin A 1 µg/ml for 5 h at 37ºC followed by intracellular IL-10 staining performed using a Transcription Factor Buffer set 14 .…”
Section: Flow Cytometrymentioning
confidence: 99%